2016
DOI: 10.1039/c6ta02036d
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of acetate from CO2by a highly structured biofilm assembled with reduced graphene oxide–tetraethylene pentamine

Abstract: A highly structured biofilm assembled with reduced graphene oxide–tetraethylene pentamine and the bacterium Sporomusa ovata performed high-rate microbial electrosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 36 publications
4
66
0
Order By: Relevance
“…The overall trend of the current in the MES with NF presented a slow decline. This phenomenon was similar to other reports . However, the current of the MES with G‐NF was stable (about 14 mA), and did not fluctuate or decline, over the whole process.…”
Section: Resultssupporting
confidence: 91%
“…The overall trend of the current in the MES with NF presented a slow decline. This phenomenon was similar to other reports . However, the current of the MES with G‐NF was stable (about 14 mA), and did not fluctuate or decline, over the whole process.…”
Section: Resultssupporting
confidence: 91%
“…The MES‐1 and MES‐2 produced maximum current of 1.88 mA and 1.6 mA, respectively in the first batch cycle and afterward the current production was noted to be decreased in both the MESs. This reduction in current in later batch cycles could be attributed to the gradual thickening of biofilm and deposition of carbonate on electrode, which are possible reason of hampering the current production . Similar declination in current production was also reported in an earlier study as well .…”
Section: Resultssupporting
confidence: 87%
“…In addition, the performance of MESs was significantly improved using nanoparticles by decreasing the activation overpotential losses during charge transfer process in redox reaction. For example, Chen et al., reported 3.6 times increase in acetate production in MES using rGO functionalized with tetraethylene pentamine catalyzed carbon cloth as compared to the untreated cathode . However, this catalyst is bit costly and can potentially poison the microbial consortia for an extended operational period and also considered as pollution threat.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] This may result in al arge amount of metal ions leachingf rom the electrocatalyst during long term operation, and thereafter cause as ignificant inhibition on bacterial growth. [29] It has been reported that many metal nanoparticlese ncapsulated within carbon nanotubes showeda higherc atalytic activity because the interactions between the metal atoms and carbon at the interfaces optimized the charged istribution and binding energy. Moreover,t he transition metals based HER catalysts generate reactive oxygen species (ROSs) in the existence of oxygen, and the generated ROSs inhibit bacterial growth.A ll these facts lead to ap oor biocompatibility of the transition-metal-based HER electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%